Adipose Stem Cells in Regenerative Medicine: Looking Forward - Al-Ghadban, Sara; Artiles, Maria; Bunnell, Bruce A. (Frontiers in Bioengineering and Biotechnology, 2022)
Over the last decade, stem cell-based regenerative medicine has progressed to clinical testing and therapeutic applications. The applications range from infusions of autologous and allogeneic stem cells to stem cell-derived products. Adult stem cells from adipose tissue (ASCs) show significant promise in treating autoimmune and neurodegenerative diseases, vascular and metabolic diseases, bone and cartilage regeneration and wound defects. The regenerative capabilities of ASCs in vivo are primarily orchestrated by their secretome of paracrine factors and cell-matrix interactions. More recent developments are focused on creating more complex structures such as 3D organoids, tissue elements and eventually fully functional tissues and organs to replace or repair diseased or damaged tissues. The current and future applications for ASCs in regenerative medicine are discussed here.